Implementation Of Fisheries Commodity Shipments From Ambon By The Company - Agusnal Fitralius Hakim; Nur Handayati; Wahyu Prawesthi; Subekti Subekti; Bachrul Amiq (JURNAL HUKUM SEHASEN, 2026)
The fisheries sector plays a strategic role in Indonesia's economic development as an archipelagic country with abundant marine resources. In addition to being a source of food, this sector is also a leading export commodity that contributes to the country's foreign exchange. Law No. 31 of 2004 stipulates that every fishing business must have a permit, and every shipment of fishery products must be accompanied by valid documents such as SKAI and quarantine certificates. However, practices in the field still show violations of these provisions, such as the shipment of fish without complete documents and not through official ports of call. Cases in Ambon show that shipments are often made in a hurry to meet export schedules, resulting in the neglect of legal aspects. This condition is exacerbated by weak supervision, limited supervisory human resources, and abuse of authority. As a result, the country stands to lose in terms of revenue and export reputation. From a criminal law perspective, such violations are punishable under Article 93 of Law No. 31 of 2004, with a maximum penalty of 6 years imprisonment and a fine of Rp 2 billion. Although administrative and criminal sanctions are available, their implementation still faces challenges in terms of enforcement and legal certainty.